779. Mycobacterium tuberculosis Prosthetic Joint Infections: A Case Series and Literature Review. (26th November 2018) - Uhel, Fabrice; Corvaisier, Grégory; Poinsignon, Yves; Chirouze, Catherine; Béraud, Guillaume; Grossi, Olivier; Varache, Nicolas; Arvieux, Cédric; Berre, Rozenn Le; Tattevin, Pierre; ,
Abstract: Background: Mycobacterium tuberculosis is a rare cause of prosthetic joint infection (PJI), as most countries with high prevalence of tuberculosis have limited access to arthroplasty. We aimed to characterize the diagnosis, the management, and the outcome of M. tuberculosis PJI. Methods: All cases of M. tuberculosis PJI documented in a network of 7 referral centers in France were retrospectively reviewed. Data were collected from medical files on a standardized questionnaire, including diagnosis, management, and outcome. In addition, we performed a systematic literature review using the keywords"prosthetic joint, " and"tuberculosis." Results: During years 1997–2016, we managed 13 patients (8 males, 5 females, median age 79 years [range, 60–86]) with documented M. tuberculosis PJI, involving hip ( n = 6), knee ( n = 6), or shoulder ( n = 1). Median time from arthroplasty to PJI diagnosis was 9 years [0.4–20]. The diagnosis was obtained on joint aspirates ( n = 9), or synovial tissue ( n = 4). PCR was positive in all cases tested (5/5). Median duration of antituberculosis treatment was 14 months [6–32]). Nine patients underwent surgery: debridement ( n = 4), definitive resection arthroplasty ( n = 3), and revision arthroplasty (1-stage exchange, n = 2). PJI was controlled in 12 patients. One patient died of disseminated tuberculosis. The literature review identified 70 additional cases of documented M. tuberculosis PJI, with a favorable outcome in 79% (11/14) of patients with no surgery, 85% (11/13) with debridement and prosthesis retention, 86% (19/22) with revision arthroplasty, and 81% (17/21) with definitive prosthesis resection (NS). Conclusion: M. tuberculosis PJI can be controlled with prolonged antituberculosis treatment in most cases, with or without surgical treatment.This case series and literature review suggest that the paradigms for the management of M. tuberculosis PJI may differ from PJI related to other pathogens, for which surgery is required. Disclosures: All authors: No reported disclosures.